1984
DOI: 10.1104/pp.75.4.1013
|View full text |Cite
|
Sign up to set email alerts
|

A High Proportion of Hybridomas Raised to a Plant Extract Secrete Antibody to Arabinose or Galactose

Abstract: A high proportion of hybridomas, obtained from mice immunized with style extracts prepared from mature flowers of an ornamental tobacco, Nicotiana alata, secrete antibody to arabinogalactan protein (AGP). The specificity of the antibodies secreted by three cloned cell lines is primarily directed to ,8-D-galactopyranose and a-L-arabinofuranose; antibodies from two cell lines preferentially bind ,-D-galactopyranose residues and antibodies from the other cell line preferentially bind a-L-arabinofuranose. As AGPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…The MAb PCBC3 (Anderson et al 1984) was purified from hybridoma supernatants by affinity chromatography on Protein-A Sepharose, giving a stock of 0.27 mg protein per ml. Rat MAb JIM5, specific for nonesterified polygalacturonan (Knox et al 1990), and the AGP-specific MAbs MAC207 (Pennell et al 1989, Pennell and, JIM8 (Pennell et al 1991), and JIM13 (Knox et al 1991) were a kind gift from Professor K. Roberts.…”
Section: Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The MAb PCBC3 (Anderson et al 1984) was purified from hybridoma supernatants by affinity chromatography on Protein-A Sepharose, giving a stock of 0.27 mg protein per ml. Rat MAb JIM5, specific for nonesterified polygalacturonan (Knox et al 1990), and the AGP-specific MAbs MAC207 (Pennell et al 1989, Pennell and, JIM8 (Pennell et al 1991), and JIM13 (Knox et al 1991) were a kind gift from Professor K. Roberts.…”
Section: Antibodiesmentioning
confidence: 99%
“…The Yariv reagent, which crosslinks AGP molecules, disrupts growth of pollen tubes of Lilium longiflorum but not Nicotiana spp., and it has been suggested that one or more AGPs may mediate insertion of newly secreted polysaccharides into the wall at the growing tube tip in Lilium Iongiflorum , Roy et al 1998. PCBC3 is a MAb raised against buffer-soluble extracts of Nicotiana styles and screened against purified stylar AGP (Anderson et al 1984), and detects AGPs in the transmitting tract (Sedgely et al 1985). From inhibition studies principally with simple sugars, PCBC3 was deduced to have a primary specificity for c~-L-arabinofuranose (c~-L-Ara~ residues (Anderson et al 1984), and labelling by PCBC3 of the outer, fibrillar wall layer of stylar-grown incompatible pollen tubes of N. alata was interpreted as due to binding to terminal (z-L-Arafresidues on arabinans (Anderson et al 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several monoclonal antibodies have been characterized as binding to arabinosecontaining epitopes (22,23). A monoclonal antibody against linear ␣1,5-arabinan oligosaccharides was reported to bind with a nanomolar affinity (24).…”
mentioning
confidence: 99%
“…The use of the synthetic peptide as an antigen obviated the difficulties previously encountered using either polyclonal or monoclona1 antibodies raised to purified Sn-glycoprotein. These difficulties of cross-reactivity with other style glycoproteins were due to the glycosyl substituents on the Sn-glycoprotein, which have saccharide sequences common to many plant glycoproteins and which are immunodominant (Howlett and Clarke, 1981; Anderson, Sandrin, and Clarke, 1984). lmmunocytochemical studies with the antipeptide antibody showed that the S2-glycoprotein is localized extracellulary in the mucilage that surrounds the transmitting tissue cells and the wall of the ovule.…”
Section: Discussionmentioning
confidence: 99%